2021
DOI: 10.3389/fphys.2021.769971
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of ACTN3 Gene Polymorphisms on Susceptibility to Exercise-Induced Muscle Damage and Changes in Running Economy Following Downhill Running

Abstract: This study aimed to investigate if ACTN3 gene polymorphism impacts the susceptibility to exercise-induced muscle damage (EIMD) and changes in running economy (RE) following downhill running. Thirty-five healthy men were allocated to the two groups based on their ACTN3 gene variants: RR and X allele carriers. Neuromuscular function [knee extensor isometric peak torque (IPT), rate of torque development (RTD), and countermovement, and squat jump height], indirect markers of EIMD [muscle soreness, mid-thigh circum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(126 reference statements)
0
3
0
Order By: Relevance
“…This shows that CK varies widely between trained individuals that perform the same training regimen. One of the main factors affecting CK values after muscle damage is presumed to be the individual polymorphism of the ACTN3 gene (Koch et al 2014 ), which was recently confirmed by de Lima et al ( 2021 ). The results of their study showed that the CK response after muscle damage is attributed to the ACTN3 polymorphism, rather than load exposure itself.…”
Section: Discussionmentioning
confidence: 93%
“…This shows that CK varies widely between trained individuals that perform the same training regimen. One of the main factors affecting CK values after muscle damage is presumed to be the individual polymorphism of the ACTN3 gene (Koch et al 2014 ), which was recently confirmed by de Lima et al ( 2021 ). The results of their study showed that the CK response after muscle damage is attributed to the ACTN3 polymorphism, rather than load exposure itself.…”
Section: Discussionmentioning
confidence: 93%
“…The loss of αactinin-3 changes the overall protein composition and elastic properties of fast myofibre Z-bands, resulting in loss of force generation and increased susceptibility to eccentric damage in αactinin-3-deficient individuals. 170,171 Other effects of the ACTN3 XX genotype related to altered muscle function and adaptation to physical demands and atrophy are observed and have been widely investigated in various human populations, with the ACTN3 XX genotype associated with age-related loss of human muscle and bone 172 and considered a disease modifier for inherited myopathies such as McArdle disease and DMD 173…”
Section: Myosin Isoformsmentioning
confidence: 99%
“…While this α‐actinin‐3 deficiency is not associated with any overt disease, it is associated with athletic performance: with detriment to optimal sprint and power performance in elite athletes and the general population, while it was initially considered beneficial for endurance athletes such as marathon runners. The loss of α‐actinin‐3 changes the overall protein composition and elastic properties of fast myofibre Z‐bands, resulting in loss of force generation and increased susceptibility to eccentric damage in α‐actinin‐3‐deficient individuals 170,171 . Other effects of the ACTN3 XX genotype related to altered muscle function and adaptation to physical demands and atrophy are observed and have been widely investigated in various human populations, with the ACTN3 XX genotype associated with age‐related loss of human muscle and bone 172 and considered a disease modifier for inherited myopathies such as McArdle disease and DMD 173 …”
Section: Neuromuscular Disorders and Myofibre‐type Manifestationmentioning
confidence: 99%